(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aims to evaluate the level of female Islamic Studies teachers familiarity with methods of combating destructive ideas in high school education in the Holy Capital of Makkah. To achieve this, the study used the descriptive analytical survey method, the study sample included (86) female Islamic Studies teachers, and used a questionnaire consisting of 12 items. The study had come to several conclusions, most importantly being: That female Islamic Studies teachers are highly familiar with destructive ideas combating methods, the study scored an arithmetic mean of (3.59), a standard deviation of (.86), and a high level of familiarity. In light of these results, the study made several recommendations.